The Effect of Telephone Health Training on Perceived Stress of Mothers with Premature Infants Discharged from Hospital - Hossein Tavangar; Marjan Alichi; Zahra Pourmovahed (Journal of Social Behavior and Community Health, 2024)
Background: Premature birth is a global health issue leading to major stress in mothers that will be able to get answers to many of their questions at home through a phone call. This study aimed to investigate the effect of telephone health training on perceived stress of mothers with premature infants discharged from hospital. Methods: This quasi-experimental study was conducted on 60 mothers referring to Shohada-ye Kargar Hospital (Yazd, Iran) in 2022. They were selected using a purposive sampling method and then randomly assigned to the control and intervention groups. Data collection was accomplished with the Perceived Stress Questionnaire and demographic questionnaire. Telephone training was performed in intervention group. The control group received the ordinary care at discharge time. Data were analyzed with SPSS22 using paired t-test, independent t-test, and chi-square test. Results: The mean perceived stress of mothers was 25.10 ± 2.32 and 25.33 ± 3.12, in the intervention and control group prior to the intervention, respectively. These scores were 21.24 ± 1.83 and 24.14 ± 2.81, respectively after the intervention, and it decreased significantly in the intervention group (P = 0.03). Conclusion: Telephone health training is regarded as an efficient and low-cost method for reducing perceived stress of mothers with premature infants discharged from the Neonatal Intensive Care Unit.  Improving maternal and neonatal health are suggested.